LEGAL PROTECTION OF CHILDREN AFTER DIVORCE DIVORCE RELATED TO ACT NUMBER 16 OF 2019 AMENDMENT TO ACT NUMBER 1 OF 1974 CONCERNING MARRIAGE (Decision Study Number 1145/pdt.g/2020/PA.Krw) - Jihan Alfadia; Muhamad Abas; Zarisnov Arafat (Justisi: Jurnal Ilmu Hukum, 2023)
Child protection is all activities to ensure and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity and values, and receive protection from violence and discrimination. Divorce so far often creates problems inherent in children's rights, namely the right to education, health, maintenance costs and so on. In Law Number 1 of 1974 concerning Marriage, it mentions the rights and obligations between parents and children. It is stated in Law Number 1 of 1974 Article 45 Paragraph 1 namely: "Both parents are obliged to look after and educate their children as well as possible, while Paragraph 2 states that: The obligations of the parents referred to in Paragraph I apply until the child marries or can stand-alone. Which obligations continue even though the marriage between the two is broked, the obligation to provide maintenance for their child is not broken and the child still gets his rights as a child. The purpose of this research is to find out the legal protection of children after divorce and to find out the considerations of judges in deciding about legal protection of children after divorce.